1979
DOI: 10.1042/cs0570427
|View full text |Cite
|
Sign up to set email alerts
|

A Micropuncture Study of Proximal Tubular Function after Acute Hydrochlorothiazide Administration to Brattleboro Rats with Diabetes Insipidus

Abstract: 1. Renal function in anaesthetized Brattleboro rats with hereditary hypothalamic diabetes insipidus was studied with micropuncture techniques before, and 1-3 h after, a single injection of hydrochlorothiazide.2. In rats given hydrochlorothiazide and kept in sodium and water balance, total glomerular filtration rate and superficial nephron filtration rate were similar to values in control animals, whereas fractional fluid reabsorption in the proximal tubule (as evidenced by tubular fluid/plasma inulin concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 7 publications
1
28
0
Order By: Relevance
“…Consistent with this notion, in a study on Brattleboro rats with central DI, Walter et al (34) showed that the antidiuresis that follows acute administration of HCTZ is entirely secondary to the natriuresis and consequent sodium depletion induced by the drug. However, Shirley et al (9) showed that the mechanism of sustained antidiuresis during chronic HCTZ administration in DI differs from that of the acute response.…”
Section: Hctz Treatment Partially Reverses Li-induced Aqp2 Downregulasupporting
confidence: 52%
“…Consistent with this notion, in a study on Brattleboro rats with central DI, Walter et al (34) showed that the antidiuresis that follows acute administration of HCTZ is entirely secondary to the natriuresis and consequent sodium depletion induced by the drug. However, Shirley et al (9) showed that the mechanism of sustained antidiuresis during chronic HCTZ administration in DI differs from that of the acute response.…”
Section: Hctz Treatment Partially Reverses Li-induced Aqp2 Downregulasupporting
confidence: 52%
“…and prepared surgically for micropuncture experiments as described in previous studies from this laboratory (Walter et al 1979, Shirley et al 1990. First, the animals were placed on a servocontrolled heated operating table to maintain the rectal temperature at 37 C. The right jugular vein was then cannulated, followed by a tracheotomy, cannulation of the right femoral artery, catherization of the bladder through a suprapubic incision and exposure of the left kidney via a flank incision.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…The animals were anaesthetized with Inactin (120 mg kg-', I.P. ; Byk Gulden, Konstanz, Germany) and prepared surgically for micropuncture as described in previous reports from this laboratory (Walter, Laycock & Shirley, 1979;Shirley, Zewde & Walter, 1990). Sodium chloride solution (150 mmol 1-l), containing LiCl (9 mmol 1-1), was infused i.v.…”
Section: General Proceduresmentioning
confidence: 99%
“…After surgery, [3H]inulin (Amersham International, Aylesbury) was included in the infusion (80 ,uCi primer; 80,uCi h-'), and after a 90 min equilibration period all animals underwent a 90 min control period. During the control period the clearances of [3H]inulin and lithium were measured and at least three micropuncture collections were made from late surface convolutions of proximal tubules (Walter et al 1979).…”
Section: General Proceduresmentioning
confidence: 99%